(untitled) (Journal of Engineering, 2008)
The inhibition of copper corrosion by Naphthylamine (NA), Ethylenediamine (EDA), Tetraethylenepentamine (TEPA), Diethylenetriamine (DETA), and Phenylenediamine (PDA) in 5% HCl have been investigated by weight loss technique at different temperatures. The results were compared with Benzotriazole (BTA), the common inhibitor used for inhibition of copper corrosion in different environments. The BTA film formed on the copper surface obeys Langmuir Adsorption Isotherm. While NA, EDA, TEPA, and DETA appear to obey the Freundlich Adsorption Isotherm. In the other hand, the two-adsorption isotherms were unsuitable to represent the data of PDA. Results also showed that the Kinetic-Thermodynamic Model was suitable to fit the experimental data of the most inhibitors of the present study.